2019
DOI: 10.1039/c9tb01492f
|View full text |Cite
|
Sign up to set email alerts
|

Low fouling and ultrasensitive electrochemical immunosensors with dual assay methods based on Fe3O4 magnetic nanoparticles

Abstract: Low fouling electrochemical immunosensors for the highly sensitive detection of cancer antigen 15-3 with both “signal-off” and “signal-on” analytical methods were developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The results showed that the amount of Fe 3 O 4 @Ag bonded to the electrode surface decreased with increasing concentration of CA 15-3, which is because of the competitive immunoreaction that causes a reduction in the detectable signals. A linear relationship between the current and the logarithm of the CA 15-3 concentration was obtained in the range of 10 to 1000 µU/mL, with a LOD of 5.2 µU/mL (Figure 2b) [70]. It is seen that the combination of the traditional electrode and a magnetic electrode could be a new strategy to generate and amplify the detecting signals for sensing.…”
Section: Pbnps For Tumor Diagnosis In Electrochemical Immunosensorsmentioning
confidence: 92%
“…The results showed that the amount of Fe 3 O 4 @Ag bonded to the electrode surface decreased with increasing concentration of CA 15-3, which is because of the competitive immunoreaction that causes a reduction in the detectable signals. A linear relationship between the current and the logarithm of the CA 15-3 concentration was obtained in the range of 10 to 1000 µU/mL, with a LOD of 5.2 µU/mL (Figure 2b) [70]. It is seen that the combination of the traditional electrode and a magnetic electrode could be a new strategy to generate and amplify the detecting signals for sensing.…”
Section: Pbnps For Tumor Diagnosis In Electrochemical Immunosensorsmentioning
confidence: 92%
“…For instance, electrochemical immunosensors able to quantify cancer antigen 15-3 in human serum were designed by using a mediated electrochemical reaction. [118] Antigens were conjugated on magnetic Fe 3 O 4 particles that were subsequently concentrated magnetically on the electrode. Electrochemical conversion of theses functional magnetic vehicles into Prussian blue enabled the transduction of targets in human serum by mediated electrochemical detection.…”
Section: Magnetically-activated Electrochemical Biosensorsmentioning
confidence: 99%
“…Therefore, several prominent developments in the fields of nucleid acid and immunosensors were achieved. For instance, electrochemical immunosensors able to quantify cancer antigen 15–3 in human serum were designed by using a mediated electrochemical reaction [118] . Antigens were conjugated on magnetic Fe 3 O 4 particles that were subsequently concentrated magnetically on the electrode.…”
Section: Recent Developments and Applicationsmentioning
confidence: 99%
“…In the literature, the common methodology and strategy to efficiently enhance signaling are to add nanomaterials, such as metal nanoparticles, 18 conductive carbon materials, 19–21 conductive polymers, 21 and metal oxides. 22,23…”
Section: Introductionmentioning
confidence: 99%